Assessment of ethnobotanical uses, household, and regional genetic diversity of aroid species grown in northeastern India - Verma, Veerendra Kumar; Kumar, Amit; Rymbai, Heiplanmi; Talang, Hammylliende; Chaudhuri, Priyajit; Devi, Mayanglambam Bilashini; Singh, Nongmaithem Uttam; Hazarika, Samrendra; Mishra, Vinay Kumar (Frontiers in Nutrition, 2023)
Aroids are an important group of indigenous tuber crops, grown widely for their leaves, petioles, stolons, corms, and cormels. A total of 53 genotypes were evaluated for their genetic diversity in northeastern region of India. At household level, a total of 16 landraces of Aroids were recorded having different ethnobotanical uses. Based on the population study under Jhum/Shifting farming, landrace Rengama was dominant in area with 47% of the total population followed by Tamachongkham and Tasakrek. However, Pugarkusu and Chigi occupied 33.0 and 24.0% of the population, respectively under backyard farming, and were considered as major landraces. Tamachongkham, high in acridity and total oxalate content (0.82%), was used for cooking with meat, while Tasakrek was used as a baby food due to high total sugar (>3.0%), low in acridity, and total oxalate content (<0.12%). The Simpson’s diversity index of the backyards was higher (0.80) as compared to Jhum field (0.63). The genotypes showed wider variability in growth and yield attributes like; plant height (89.4–206.1 cm), number of side shoots (1.84–5.92), corm weight (38.0–683.3 g), cormel weight (14.0–348.3 g), yield (0.24–1.83 kg plant−1). Similarly, wide variations were also observed for quality traits like total sugar (1.93–4.94%); starch (15.32–32.49%), total oxalate (0.10–0.82%), and dry matter (16.75–27.08%) content. Except for total oxalate, all the growth and yield attributes have shown high heritability and moderate to high genetic advance. Molecular analysis (33 polymorphic SSR markers) detected a total of 136 alleles, ranged 3 to 8 alleles per marker. The observed heterozygosity (0.24) was less than expected heterozygosity (0.69). The group-wise maximum genetic divergence was observed between Colocasia fallax (cv. Chigi) to C. esculenta var. aquatilis (cv. Tharsing); C. fallax (cv. Chigi) to C. gigantea (cv. Ganima) and C. gigantea (cv. Ganima) to Xanthosoma spp., while it was least between eddo and dasheen. The findings indicated, a wider diversity and distinct ethnobotanical uses of Aroid landraces at the house hold levels, which should be conserved and popularized to ensure nutritional security.